Real-world clinical outcomes of nivolumab and taxane as a second- or later-line therapy for recurrent or unresectable advanced esophageal squamous cell carcinoma - Ohsawa, Manato; Hamai, Yoichi; Emi, Manabu; Ibuki, Yuta; Kurokawa, Tomoaki; Yoshikawa, Toru; Hirohata, Ryosuke; Kitasaki, Nao; Okada, Morihito (Frontiers in Oncology, 2023)
Background: Nivolumab is approved in Japan as a second-line treatment for patients with advanced esophageal squamous cell carcinoma (ESCC) resistant to fluoropyrimidine and platinum-based drugs. It is also used in adjuvant and primary postoperative therapies. This study aimed to report real-world data on nivolumab use for esophageal cancer treatment. Methods: In total, 171 patients with recurrent or unresectable advanced ESCC who received nivolumab (n = 61) or taxane (n = 110) were included. We collected real-world data of patients treated with nivolumab as a second- or later-line therapy and evaluated treatment outcomes and safety. Results: Median overall survival was longer and progression-free survival (PFS) was significantly longer (p = 0.0172) in patients who received nivolumab than in patients who received taxane as a second- or later-line therapy. Furthermore, subgroup analysis for second-line treatment only showed the superiority of nivolumab in increasing the PFS rate (p = 0.0056). No serious adverse events were observed. Conclusions: In real-world practice, nivolumab was safer and more effective than taxane in patients with ESCC with diverse clinical profiles who did not meet trial eligibility criteria, including those with poor Eastern Cooperative Oncology Group performance status, comorbidities, and receiving multiple treatments.